Corporate network reliability optimization - Dimova, Rozalina; Stoyanov, Nikolai; Kadrev, Vasil (Yearbook Telecommunications, 2014)
The paper presents a study of the corporate network reliability depending on the protocols used, the topology and reservation of the network. The results show that reliability of enterprise networks need backup of key network elements at a higher hierarchy level.